Reinforced Concrete Structures: Analysis and Design - Fanella, David A. (New York : McGraw-Hill Education Blacklick : McGraw-Hill Companies, The [Distributor], 2015)
Annotation This is a valuable, practical guide to mastering the basics of reinforced concrete design. It introduces engineers, architects and students to the analysis, design, and detailing of cast-in-place, non-pre-stressed concrete structures that are located in areas of low seismic risk.
(3SjO GdJhfSi (B/ (3cdjI GdgfOSIs
Trade